Study design and rationale for the Olpasiran trials of Cardiovascular Events And lipoproteiN(a) reduction-DOSE finding study (OCEAN(a)-DOSE) - O'Donoghue, Michelle L.; G． López, J. Antonio; Knusel, Beat; Gencer, Baris; Wang, Huei; Wu, You; Kassahun, Helina; Sabatine, Marc S. (The American heart journal, 2022)
Data support lipoprotein(a) (Lp[Lp(a)]) being a risk factor for atherosclerotic cardiovascular disease (ASCVD). Olpasiran is a small interfering RNA molecule that markedly reduces Lp(a) production in hepatocytes. The Olpasiran trials of Cardiovascular Events And lipoproteiN(a) reduction-DOSE finding study is a multicenter, randomized, double-blind, placebo-controlled dose-finding study in 281 subjects with established ASCVD and Lp(a) > 150 nmol/L. Patients were randomly allocated to one of 4 active subcutaneous doses of olpasiran (10 mg q12 weeks, 75 mg q12 weeks, 225 mg q 12 weeks, or 225 mg q24 weeks) or matched placebo. The primary objective is to evaluate the effects of olpasiran dosed every 12 weeks compared with placebo on the percent change in Lp(a) from baseline at 36 weeks. Enrollment is now complete and follow-up is ongoing. OCEAN(a)-DOSE trial is assessing the Lp(a)-lowering efficacy and safety of olpasiran. These data will be used to determine optimal dosing and design for a cardiovascular outcomes trial.